A Review on Patch Based Image Restoration or Inpainting - Singh, K; Shaveta, J (International Journal of Computer Sciences and Engineering, 2025)
Blocking artefacts occurs almost in every compression technology including the most renowned JPEG compression. To minimize the blocking artefact problem, several researches have been done. But adaptively lacks in those algorithms which leads to complex calculation and distortion in the image. In this paper, we have proposed adaptive neighbourhood selection in a way that balances the exactness of approximation. The proposed method is iterative and spontaneously adapts to the degree of underlying smoothness. Our proposed method also restores distorted cracked images along with compressed blocking artefacts.